Hypnobreasfeeding and Massage Effluarge with Clary Sage Oil to Increase Breast Milk Production for Public Mothers: Hypnobreasfeeding dan Massage Effluarge dengan Clary Sage Oil untuk Meningkatkan Produksi Asi Ibu Nifas - Hamidah, Anisa Nur; Kusumastuti, K; Prabandari, Fitria (Prosiding University Research Colloquium, 2023)
Introduction: The achievement of exclusive breastfeeding in Kebumen Regency in 2021 is 87.67%. One of the causes of not giving exclusive breastfeeding for babies under six months of age is the production of breast milk for postpartum mothers, which is hampered or not smooth in the early days after giving birth. The impact of not exclusive breastfeeding until the baby is six months old is the lack of proper child growth and development. Hypnobreasfeeding and Massage Effluarge can be an alternative for breastfeeding mothers to increase milk production because relaxation techniques can relax and calm so that the release of the hormone oxytocin occurs so that breast milk becomes smooth. Purpose: To increase milk production, implementing Hypnobreasfeeding and efflurge massage for postpartum mothers. Results: The application was carried out for six days from 6 hours after giving birth; participants were given Hypnobreasfeeding and massage effleurage every day. After implementing Hypnobreasfeeding and massage effleurage for six days, there was an increase in milk production with the category fulfilled for the five participants. Before being given the application, the milk production of the five participants was in the unfulfilled category. Conclusion: The application of hypnobreasfeeding and effleurage massage has an effect on facilitating breasfeeding in postpartum mothers.